Nickel fluoride as a surface activation agent for electroless nickel coating of anodized AA1050 aluminum alloy - Kocabas, M.; Ornek, C.; Curioni, M.; Cansever, N. (ELSEVIER SCIENCE SA, 2019)
In this study, the use of nickel fluoride tetrahydrate (NiF2 center dot 4H(2)O) as a surface activator and sealant at the same time for the coating of electroless nickel-phosphorus (Ni-P) on anodized aluminum alloy AA1050 is proposed. The usage of the activator resulted in more efficient deposition of Ni-P, improved adhesion properties, and increased wear and friction behavior as opposed to non-activated conditions. Scanning electron microscopy (SEM) and confocal laser microscopy (CLM) analyses of ultramicrotome-cut cross sections of Ni-P coated specimens, surface-activated by NiF2 center dot 4H(2)O, revealed a more well-structured metal-coating interface as opposed to non-activated conditions.
Keywords: Nickel fluoride tetrahydrate (NiF2 center dot 4H(2)O); Aluminum alloy; Anodizing; Electroless nickel-phosphorus coating (Ni-P); Surface activation; Scratch test; NI-P; FILMS; COMPOSITE; LAYERS; OXIDE; PRETREATMENT; ADHESION; METAL; XPS; Materials Science; Physics